Epidemiological and molecular profile of lung cancer patients in a referral cancer center in Lima, Peru - Motta Guerrero, Rodrigo (2023)
Background: According to GLOBOCAN estimates, in 2020, lung cancer was the second most frequent cancer and epidemiological information is needed in Latin American countries. The objective was to describe the epidemiological and molecular characteristics of lung cancer patients from a referral clinic in Lima, Peru. Material and methods: A retrospective cohort study was conducted to characterize the epidemiological and molecular profile of lung cancer patients attended at a referral cancer center in Peru during 2018 to 2021. Variables such as age, sex, histology, staging and mutation were reported. In the descriptive analysis, frequencies and percentages were shown for categorical variables. For numerical variables, the best measure of central tendency and dispersion was reported. Results: A total of 225 patients with a diagnosis of lung cancer were observed. EGFR gene mutation was the most frequently detected (45.3%); and within them exon 19 deletion (55.7%). The most frequent histological type was adenocarcinoma with 180 patients (85.7%). Of the total number of patients with EGFR mutation, 77.8% received treatment with a tyrosine kinase inhibitor (osimertinib, erlotinib, afatinib) and 15.9% received immunotherapy (pembrolizumab, atezolizumab, nivolumab). Conclusions: The predominant mutation was EGFR, the most frequent histologic type was adenocarcinoma and most patients received treatment with a tyrosine kinase inhibitor.